The therapeutic efficacy of mesenchymal stem cells and their extracellular vesicles in the treatment of diverse skin diseases - Matwiejuk, Mateusz; Mikłosz, Agnieszka; Myśliwiec, Hanna; Chabowski, Adrian; Flisiak, Iwona (Frontiers in Immunology, 2025)
This review presents the current knowledge on the potential of mesenchymal stem cells (MSCs) and their extracellular vesicles (EVs) in the treatment of various skin diseases such as psoriasis, atopic dermatitis, contact dermatitis, systemic sclerosis, graft-versus-host disease, alopecia areata, and systemic lupus erythematosus. MSCs can modulate the immune response and release growth factors and cytokines that promote tissue regeneration and healing and reduce inflammation. In turn, EVs’ ability to transport various biological molecules, including microRNAs (miRNAs), makes them potential therapeutic agents. Moreover, EVs have been shown to reduce scaling, thickness, and erythema in psoriasis. In atopic dermatitis, EVs can alleviate clinical symptoms, lower serum IgE levels, and reduce immune cell infiltration. Mesenchymal stem cells like bone marrow-derived mesenchymal stem cells (BM-MSCs) exert their immunomodulatory effects by directly targeting various immune cell populations, including T cells, B cells, dendritic cells, and natural killer (NK) cells. To fully realize the potential of EVs in clinical practice, further research is needed to conduct well-designed clinical trials to evaluate the safety and efficacy of EV-based therapies in different skin diseases. Overall, EVs have the potential to revolutionize the treatment of skin diseases by offering a targeted and effective approach to address various underlying mechanisms, although further large-scale studies are needed.